2018
DOI: 10.21873/invivo.11261
|View full text |Cite
|
Sign up to set email alerts
|

Considerations Regarding Embryo Culture Conditions: From Media to Epigenetics

Abstract: Media were first produced in-house with limited quality control, now they are commercially and widely available containing nutrients, vitamins and growth factors and strictly produced by manufacturers who follow specific quality 451

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 94 publications
(107 reference statements)
0
15
0
2
Order By: Relevance
“…During oocyte maturation and early embryo development, various enzymes and metabolic pathways produce endogenous reactive oxygen species (ROS) [46]. The accumulation of ROS in cells leads to cell membrane lipid peroxidation, blockade of RNA transcription, damage of DNA and decreases in protein synthesis [47,48,49]. It has been reported that oxidative stress can induce ER stress and UPR signaling by impeding correct protein folding and calcium homeostasis [50].…”
Section: Activation and Induction Of Endoplasmic Reticulum Stress mentioning
confidence: 99%
“…During oocyte maturation and early embryo development, various enzymes and metabolic pathways produce endogenous reactive oxygen species (ROS) [46]. The accumulation of ROS in cells leads to cell membrane lipid peroxidation, blockade of RNA transcription, damage of DNA and decreases in protein synthesis [47,48,49]. It has been reported that oxidative stress can induce ER stress and UPR signaling by impeding correct protein folding and calcium homeostasis [50].…”
Section: Activation and Induction Of Endoplasmic Reticulum Stress mentioning
confidence: 99%
“…Prior to applying CM in human ARTs, it is required that the efficacy and toxicity of the materials are evaluated in animal models, allowing for insufficiency and ethical issues on human embryo [27,28]. Mouse preimplantation embryos are generally used to examine the development of culture medium owing to their developmental similarity to humans [29]. In the present study, using in vitro fertilized mouse embryos, we aimed to evaluate the anti-oxidative and anti-apoptotic effects of human ASC-CM with optimal basal medium by comparing KSFM and DMEM, and its ability as supplements to improve preimplantation embryo development during IVC.…”
Section: Introductionmentioning
confidence: 99%
“…The temperature was set based on the literature and our preliminary study. The literature demonstrated that slightly lower temperature could be physiologically relevant to reproductive tissues [ 32 , 33 , 34 ] and comparable to traditional 37 °C for reproductive outcomes [ 35 , 36 , 37 ]. In our preliminary study, developmental rate to BL at 36 °C showed no difference to that at 37 °C, and both rates were observed within the normal range.…”
Section: Methodsmentioning
confidence: 99%